2007
DOI: 10.1590/s0103-50532007000800003
|View full text |Cite
|
Sign up to set email alerts
|

Cationic dyes immobilized on cellulose acetate surface modified with titanium dioxide: factorial design and an application as sensor for NADH

Abstract: As propriedades eletroquímicas dos corantes catiônicos, azul de meldola e azul de toluidina, imobilizados na superfície do acetato de celulose modificado com dióxido de titânio foram investigadas por voltametria cíclica. Os materiais sintetizados foram empregados como eletrodos de pasta de carbono. As propriedades mediadoras redox dos eletrodos modificados quimicamente com azul de meldola e azul de toluidina foram otimizadas utilizando um planejamento fatorial consistindo de dois níveis e quatro fatores com do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…of biosensors based on dehydrogenase, due to its ability to mediate the oxidation of nicotinamide adenine dinucleotides [37][38][39][40][41][42][43]. Cobalt Phthalocyanine, an organic semiconductor ensuring sensor stability and sensitivity is another modifier used in the development of CMEs [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…of biosensors based on dehydrogenase, due to its ability to mediate the oxidation of nicotinamide adenine dinucleotides [37][38][39][40][41][42][43]. Cobalt Phthalocyanine, an organic semiconductor ensuring sensor stability and sensitivity is another modifier used in the development of CMEs [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…This oxide combined with the polymer increases its adsorbent properties and even renders it suitable for application as an antibacterial agent 17 . This composite is applied as a microfiltration membrane 12 , enzyme immobilisation support material [18][19][20] , an enhancer of the biological properties of haemostatic agents 21 , as an adsorbent of organic dyes, and in electrochemical sensors 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The nature of supporting electrolyte that was changed by varying the cation and anion (phosphate buffer, KCl, NH4Cl, NaNO3 and NH4NO3) did not produce any significant influence on E1/2. Such results suggested that these supporting electrolytes are not interacting with the matrix surface and produce no significant change of the midpoint potential [20].…”
Section: Electrochemical Studiesmentioning
confidence: 91%